2021
DOI: 10.2147/ijgm.s338797
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Comprehensive Analysis of a ceRNA Immunoregulatory Network and Tissue-Infiltrating Immune Cells in Atrial Fibrillation

Abstract: Background: At present, the mechanisms behind atrial fibrillation (AF) pathogenesis are still unclear. We construct a ceRNA immunoregulatory network to further understand the mechanism of AF. Methods: Four AF mRNA datasets from the Gene Expression Omnibus (GEO) database were integrated by SVA method. AF-related immune genes (AF-IRGs) were selected via combining ImmPort database with the genes in the module most associated with AF obtained by a weighted gene coexpression network analysis (WGCNA). Then, circRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, the speci c underlying mechanisms of these genes in AF require further clari cation. [24,25]. Our study indicates that hsa-miR-129-5p, hsa-miR-495-3p, hsa-miR-200c-3p, hsa-miR-92b-3p, and hsa-miR-429 are involved in the pathophysiological processes of atrial brillation (AF), suggesting their potential as targets for the prevention and treatment of AF.…”
Section: Disscusionmentioning
confidence: 89%
“…However, the speci c underlying mechanisms of these genes in AF require further clari cation. [24,25]. Our study indicates that hsa-miR-129-5p, hsa-miR-495-3p, hsa-miR-200c-3p, hsa-miR-92b-3p, and hsa-miR-429 are involved in the pathophysiological processes of atrial brillation (AF), suggesting their potential as targets for the prevention and treatment of AF.…”
Section: Disscusionmentioning
confidence: 89%
“…And they validated IL-6-miR-210 inhibits Tregs function by targeting Foxp3 to promote atrial fibrosis. Recently, we downloaded immune genes from the database and constructed the immune cell-related ceRNA subnetwork through bioinformatics analysis, which the results showed that Tregs were also underexpressed in atrial auricular tissue of AF [ 37 ]. One more study revealed that Tregs alleviate myocardial fibrosis and cardiac hypertrophy in hypertensive mice caused by angiotensin II [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2022) pointed out four other hub genes, including CXCL12, LTBP1, LOXL1, and IGFBP3 [ 56 ]. The cytokine CXCL12, which recruits monocytes and lymphocytes, was also indicated by Liu et al (2021) as a hub DEG in AF along with IL7R, TNFSF13B, and CD8A associated with regulatory T cells or natural killer-cell-activated immune cells [ 57 ]. These data show that CXCL12 plays a vital role in regulating the local inflammatory response and immune cell infiltration.…”
Section: Inflammation and Immune Systemmentioning
confidence: 99%